Application of ceramsite and activated alumina balls as recyclable bulking agents for sludge composting. (March 2019) - Wang, Xiankai; Zheng, Guodi; Chen, Tongbin; Nie, Erqi; Wang, Yuewei; Shi, Xiaoxiao; Liu, Junwan
Abstract: Composting is a major sludge-treatment method and bulking agents are very important in sludge composting. In this study, ceramsite and activated alumina balls were chosen as recyclable bulking agents for sludge composting. Variations in the temperature, pH, electrical conductivity, organic matter, dissolved organic carbon, moisture content, and heavy metals were detected during composting with different bulking-agent treatments as well as differences in the germination index values. The results showed that both bulking agents could ensure the maturity of the compost; further, ceramsite treatment resulted in the best water removal efficiency. According to the sequential extraction procedure, both ceramsite and activated alumina balls could stabilize Cd but they also increased the mobility of Zn. After comparing the effects of different particle sizes of ceramsite on composting, 20 mm was determined to be the most optimal value. Additionally, the recovery rates of ceramsite and activated alumina balls were 96.9% and 99.9%, respectively. Graphical abstract: Image 1 Highlights: Ceramsite and AAB were chosen as recyclable bulking agents for composting. Ceramsite improved organic matter degradation and water removal during composting. Both ceramsite and AAB stabilised Cd in sludge by compost treatment. Optimal particle size of ceramsite for use as a composting bulking agent was 20 mm. Both ceramsite and AAB had good recycling potential as bulking agents for composting.